Maladaptive Contractility of 3D Human Cardiac Microtissues to Mechanical Nonuniformity. Issue 8 (23rd February 2020) - Wang, Chenyan; Koo, Sangmo; Park, Minok; Vangelatos, Zacharias; Hoang, Plansky; Conklin, Bruce R.; Grigoropoulos, Costas P.; Healy, Kevin E.; Ma, Zhen
Abstract: Cardiac tissues are able to adjust their contractile behavior to adapt to the local mechanical environment. Nonuniformity of the native tissue mechanical properties contributes to the development of heart dysfunctions, yet the current in vitro cardiac tissue models often fail to recapitulate the mechanical nonuniformity. To address this issue, a 3D cardiac microtissue model is developed with engineered mechanical nonuniformity, enabled by 3D‐printed hybrid matrices composed of fibers with different diameters. When escalating the complexity of tissue mechanical environments, cardiac microtissues start to develop maladaptive hypercontractile phenotypes, demonstrated in both contractile motion analysis and force‐power analysis. This novel hybrid system could potentially facilitate the establishment of "pathologically‐inspired" cardiac microtissue models for deeper understanding of heart pathology due to nonuniformity of the tissue mechanical environment. Abstract : Native heart tissues adjust their function when experiencing nonuniform mechanical environments caused by heart diseases (e.g., partial fibrosis). A 3D cardiac microtissue model under a nonuniform mechanical environment is developed by combining fibers with high or low mechanical resistance. This "pathologically‐inspired" 3D in vitro cardiac microtissue model allows for the probing of the adaptivity of cardiac microtissues to nonuniform tissue mechanical environments.